SARS-CoV-2: fate in water environments and sewage surveillance as an early warning system - Deepak Panchal (IWA Publishing, 2021)
Coronavirus disease has emerged as one of the greatest threats to human well-being. Currently, the whole world is fighting against this pandemic that is transmitted either through exposure to virus laden respiratory or water droplets or by touching the virus contaminated surfaces. The viral load in feces of an infected patient varies according to the severity of the disease. Subsequent detection of viral genome (SARS-CoV-2) in human feces and sewage systems is an emerging concern for public health. This also dictates to reinforce the existing sewage/wastewater treatment facilities. Rapid monitoring is the key to prevent and control the current mass transmission. Wastewater-based epidemiology (WBE) is a potential epidemiology tool that can act as a complementary approach for current infectious disease surveillance systems and an early warning system for disease outbreaks. In a developing country like India, inadequate wastewater treatment systems, low-operational facility and relaxed surface water quality criteria even in terms of fecal coliform bacteria are the major challenges for WBE. Herein, we review the occurrence, transmission, and survival of SARS-CoV-2, and disinfection and potential of sewage surveillance as an early warning system for COVID-19 spread. We also discuss the challenges of open-defecation practices affecting sewage-surveillance in real-time in densely populated developing countries like India. HIGHLIGHTS Fate of SARS-CoV-2 in water environment is discussed.; Trend and reinfection in community can also be revealed by sewage-based epidemiology.; Sewage surveillance can serve as an early warning system.; Robust sampling strategies with subsequent rapid detection methods are crucial.; Open-defecation activities make the available WWTPs less representative and hamper the real-time sewage monitoring.;